Influence of nutrients and metabolites on the differentiation of plasma cells and implications for autoimmunity - Föh, Bandik; Buhre, Jana Sophia; Sina, Christian; Ehlers, Marc (Frontiers in Immunology, 2022)
The modulation of inflammatory (auto)immune reactions by nutrients and gut bacterial metabolites is of great interest for potential preventive and therapeutic strategies. B cell-derived plasma cells are major players in inflammatory (auto)immune responses and can exhibit pro- or anti-inflammatory effects through (auto)antibody-dependent and -independent functions. Emerging evidence indicates a key role of nutrients and microbial metabolites in regulating the differentiation of plasma cells as well as their differentiation to pro- or anti-inflammatory phenotypes. These effects might be mediated indirectly by influencing other immune cells or directly through B cell-intrinsic mechanisms. Here, we provide an overview of nutrients and metabolites that influence B cell-intrinsic signaling pathways regulating B cell activation, plasma cell differentiation, and effector functions. Furthermore, we outline important inflammatory plasma cell phenotypes whose differentiation could be targeted by nutrients and microbial metabolites. Finally, we discuss possible implications for inflammatory (auto)immune conditions.